Health Education Services in the Selected District Hospitals: Service Providers and Service Receivers Perspective (Update Dental College Journal, 2022)
This descriptive cross-sectional study was carried out for one year in two district hospitals under Dhaka division among 71 service providers and 135 service receivers with the aim of assessing the status of health education services in district hospitals from both service receivers and service providers' perspective. Data was collected from the respondents through face-to-face interviews using a pretested semi-structured questionnaire. The study revealed that health education was provided in the district hospitals mainly by nurses (78.9%), followed by physicians (14.1%) and health education officers (7.0%). Among them, 54.9% were trained in health education. They were providing health education on environmental and personal hygiene, food and nutrition, immunization, diarrhoea, breast feeding, antenatal care, postnatal care, tuberculosis and pneumonia through different methods. In spite of having limitations on health education support services, most of the service receivers were satisfied with the cooperation as well as the media or methods of health education used by the service providers during health education sessions. The findings of this study may be useful for the improvement of the health education service status in the district level hospitals.Update Dent. Coll. j: 2022; 12(2): 3-6